STUDI EFEK MEMORI HIDROKSIDA GANDA TERLAPIS Zn-Al-NO3 - Tias Ernawati; Roto Roto (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
Synthesis and memory effectâ€™s study of Zn-Al Layered Double Hydroxides (LDH) containing nitrite anion had been performed. Zn-Al-NO3 LDH were synthesized by coprecipitating and hydrothermal methods with molar ratio of Zn:Al of 3:1. The conversion of Zn-Al-NO3 LDH to corresponding mixed metal oxide were carried out by heating Zn-Al-NO3 LDH at 400Âº C for 2 hours. The reconstruction of Zn-Al-NO3 LDH were carried out by reacting the mixed metal oxide with solution of sodium nitrate 0,01 mol.Zn0.702Al0.298(OH)2(NO3)0.298.1.882H2O were synthesized. Its mixed metal oxide were made. The results of XRD and FTIR analyses showed that Zn-Al-NO3 LDH could be reconstructed after calcination. This work may enable to recycle and reuse of LDHs after the structure damaged.